KONSEP PERIJINAN BERWAWASAN LINGKUNGAN DALAM MEWUJUDKAN PEMBANGUNAN BERKELANJUTAN - Miarmi, Ni Luh Putu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 3 No 1 (2014)DO - 10.24843/JMHU.2014.v03.i01.p08, 2014)
The need for a healthy and sustainable environment into hope everyone all the time. The development of rapid development as a result of the fulfillment of the needs  of  life  with  varying  levels  of  need  have  an  impact  on  the  use  and management of the environment. Based on this paradigm and the use of environmental management is expected to meet the needs of the present without compromising the rights needs of future generations. Governments in the concept of the welfare  state law permitted  to intervene  in an effort  to meet the public welfare through  licensing  instrument  is intended  as a means of preventing  the destruction of the environment.
Keywords: environmental, permitting, sustainable development